A New Covert Channel over Cellular Voice Channel in Smartphones - Aloraini, Bushra; Johnson, Daryl; Stackpole, Bill; Mishra, Sumita (2015)
Investigating network covert channels in smartphones has become increasingly important as smartphones have recently replaced the role of traditional computers. Smartphones are subject to traditional computer network covert channel techniques. Smartphones also introduce new sets of covert channel techniques as they add more capabilities and multiple network connections. This work presents a new network covert channel in smartphones. The research studies the ability to leak information from the smartphones applications by reaching the cellular voice stream, and it examines the ability to employ the cellular voice channel to be a potential medium of information leakage through carrying modulated speech-like data covertly. To validate the theory, an Android software audio modem has been developed and it was able to leak data successfully through the cellular voice channel stream by carrying modulated data with a throughput of 13 bps with 0.018% BER. Moreover, Android security policies are investigated and broken in order to implement a user-mode rootkit that opens the voice channels by stealthily answering an incoming voice call. Multiple scenarios are conducted to verify the effectiveness of the proposed covert channel. This study identifies a new potential smartphone covert channel, and discusses some security vulnerabilities in Android OS that allow the use of this channel demonstrating the need to set countermeasures against this kind of breach.